2019
DOI: 10.1101/631861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-autonomous regulation of epithelial cell quiescence by calcium channel Trpv6

Abstract: Epithelial homeostasis and regeneration require a pool of quiescent cells. How the quiescent cells are established and maintained is poorly understood. Here we report that Trpv6, a cation channel responsible for epithelial Ca 2+ absorption, functions as a key regulator of cellular quiescence. Genetic deletion and pharmacological blockade of Trpv6 promoted zebrafish epithelial cells to exit from quiescence and re-enter the cell cycle. Reintroducing Trpv6, but not its channel dead mutant, restored the quiescent … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…The Trpv6-mediated Ca 2+ uptake and IGF signaling are likely linked. In a recent study, we have shown that Trpv6mediated constitutive Ca 2+ influx promotes cell quiescence state by suppressing IGF signaling (Xin et al, 2019). In this study, we found that the elevated NaR cell reactivation in the stc1a -/-mutant fish requires Trpv6.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The Trpv6-mediated Ca 2+ uptake and IGF signaling are likely linked. In a recent study, we have shown that Trpv6mediated constitutive Ca 2+ influx promotes cell quiescence state by suppressing IGF signaling (Xin et al, 2019). In this study, we found that the elevated NaR cell reactivation in the stc1a -/-mutant fish requires Trpv6.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, we investigated the impact of Ca 2+ states on the 4 stc genes in zebrafish. In addition of manipulating [Ca 2+ ] in the media as an indirect way to alter body Ca 2+ levels, we also utilized trpv6 -/and papp-aa -/mutant fish, which have been shown to be hypocalcemic (Liu et al, 2020;Xin et al, 2019). Our data suggest that the expression of stc1a, but not other stc genes, is regulated in a effect, suggesting the MAP kinase pathway does not play a major role.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations